Penurunan gastric residual volume, distensi abdomen, dan frekuensi muntah pada bayi prematur terpasang ventilasi mekanik dengan abdominal massage - Ardiansyah, Diki; Kadi, Fiva Aprillia; Rudhiati, Fauziah; Setiasih, Yani (Holistik Jurnal Kesehatan, 2025)
Background: Feeding intolerance (FI) is a common problem found in premature infants <34 weeks. Prematurity and the effects of mechanical ventilation are the causes of this incident. The main impacts that occur due to FI include delays in providing complete feeding, NEC, infection, increased length of hospital stay (LOS), and treatment costs. Abdominal massage is one of the recommended actions to prevent and overcome this. Purpose: To analyze the reduction of gastric residual volume, abdominal distension, and vomiting frequency in premature infants using mechanical ventilation with abdominal massage. Method: Quasy experiment study with non-equivalent control group pretest and posttest. The study was conducted on 60 premature babies and divided into 30 intervention groups and 30 control groups. Symptoms of feeding intolerance include gastric residual volume (GRV), abdominal distension, and frequency of vomiting which were observed daily until the 5th day before and after the intervention. Abdominal massage was performed 2x/day for 15 minutes and was carried out for 5 days. Data analysis from the first day to the 5th day. Results: The average amount of gastric residue was -0.70 cc in the intervention group and +3.23 in the control group (p<0.05). The average difference also occurred in the size of abdominal distension of -0.20 cm in the intervention group and +1.77 cm (p <0.05). While the frequency of vomiting did not experience a significant difference in the two groups (p = 0.74). Conclusion: Gastric Residual Volume, Vomiting Frequency, and Abdominal Distension in premature infants on mechanical ventilation can be reduced and prevented by implementing abdominal massage.   Keywords: Abdominal Distension; Abdominal Massage; Gastric Residual Volume; Premature Infants; Vomiting Frequency.   Pendahuluan: Feeding intolerance (FI) merupakan masalah yang sering ditemukan pada bayi prematur <34 minggu. Prematuritas dan efek dari pemasangan ventilasi mekanik menjadi penyebab kejadian tersebut. Dampak besar yang terjadi akibat FI seperti penundaan full feeding, NEC, infeksi, peningkatan lama rawat inap (LOS), dan biaya perawatan. Abdominal massage salah satu tindakan yang direkomendasikan untuk mencegah dan mengatasi hal tersebut. Tujuan: Untuk menganalisis penurunan gastric residual volume, distensi abdomen, dan frekuensi muntah pada bayi prematur terpasang ventilasi mekanik dengan abdominal massage. Metode: Penelitian quasi experiment dengan non-equivalent control group pretest dan post test. Penelitian dilakukan kepada 60 bayi prematur dan terbagi menjadi 2 kelompok, 30 sampel kelompok intervensi dan 30 sampel kelompok kontrol. Gejala feeding intolerance diantaranya nya gastric residual volume (GRV), distensi abdomen, dan frekuensi muntah yang diobservasi setiap hari sampai hari ke 5 sebelum dan setelah dilakukan intervensi. Abdominal massage dilakukan 2x/hari selama 15 menit dan dilakukan selama 5 hari. Data analisis sejak hari pertama sampai hari ke 5. Hasil: Rata-rata jumlah residu lambung sebesar -0.70 cc pada kelompok intervensi dan +3.23 pada kelompok kontrol (p<0.05). Perbedaan rata-rata pun terjadi pada ukuran distensi abdomen sebesar -0.20 cm pada kelompok intervensi dan +1.77 cm (p < 0.05). Sedangkan frekuensi muntah tidak mengalami perbedaan yang signifikan pada kedua kelompok (p = 0.74). Simpulan: Gastric residual volume, frekuensi muntah, dan distensi abdomen pada bayi prematur terpasang ventilasi mekanik dapat diturunkan dan dicegah dengan mengimplementasikan abdominal massage.   Kata Kunci: Abdominal Massage; Bayi Prematur; Distensi Abdomen; Frekuensi Muntah; Gastric Residual Volume.